Decline in HIV seroprevalence in street youth 2006–2012, St. Petersburg, Russia: moving toward an AIDS-free generation. (March 2017) - Kornilova, Marina S; Batluk, Julia V; Yorick, Roman V; Baughman, Andrew L; Hillis, Susan D; Vitek, Charles R
A 2006 survey of street youth at pre-mapped street youth locations in St. Petersburg, Russia, found extremely high HIV seroprevalence (37.4%) among 313 street youth aged 15–19 years of age, strongly associated with injection drug use, which was reported by 50.6% of participants. In response, multi-sectoral social support and prevention measures were instituted. In 2012, we conducted a follow-up survey of 15- to 19-year-old street youth using the same study procedures as in 2006. Of 311 participants, 45 (14.5%) reported injection drug use; 31 participants (10.0%, 95% confidence interval, 6.0%–16.2%) were HIV-seropositive . Predictors independently associated with HIV seropositivity included injection drug use (adjusted prevalence ratio 53.1) and transactional sex (adjusted prevalence ratio 1.3). None of the 178 participants aged 15–17 years were HIV-positive. Thirty of 31 (96.8%) HIV-seropositive individuals reported injection drug use. Street youth in St Petersburg had a 73% decrease in HIV seroprevalence from 2006 to 2012, primarily due to decreased initiation of injection drug use. This marked reduction in the HIV epidemic among street youth occurred after implementation of extensive support programs and socio-economic improvements.